GOLPH3 inhibits glioma cell apoptosis through the JNK signaling pathway - Xie, Shao; Ding, Jiahai; Wang, Zhaohao; Shi, Hengliang; Yu, Zheng-Quan (Frontiers in Genetics, 2025)
BackgroundGlioma, a primary intracranial tumor, is marked by high rates of mortality and disability, making it a significant health concern. Understanding the molecular mechanisms underlying glioma initiation and progression and identifying potential therapeutic targets for gene therapy are crucial for improving patient outcomes. Golgi phosphoprotein 3 (GOLPH3), predominantly localized at the trans-Golgi network, has been implicated in the pathogenesis of various cancers. However, its precise role in glioma progression remains under active investigation.MethodsTo elucidate the function of GOLPH3, U87 glioma cells were transfected with GOLPH3-specific small interfering RNA (siRNA) to suppress its expression. An in vivo glioma model was generated by implanting GOLPH3-knockdown U87 cells into nude mice. Apoptosis was assessed using flow cytometry, immunofluorescence staining, TUNEL assays, and Western blotting. The activation of the JNK signaling pathway was evaluated by analyzing the phosphorylation levels of JNK and c-Jun through Western blotting.ResultsDownregulation of GOLPH3 in U87 glioma cells significantly enhanced apoptosis, as evidenced by increased levels of cleaved caspase-3 and higher apoptosis rates. Furthermore, GOLPH3 knockdown led to the activation of the JNK signaling pathway, as indicated by elevated phosphorylation of JNK and c-Jun. In vivo, suppression of GOLPH3 expression inhibited tumor growth and increased apoptosis within the tumor microenvironment.ConclusionThese findings suggest that GOLPH3 might play a pivotal role in regulating apoptosis in malignant glioma cells via the JNK signaling pathway. Thus, GOLPH3 may represent a promising therapeutic target for glioma treatment.